2014
DOI: 10.1093/gbe/evu184
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Deep Regulatory Similarities in Early Developmental Programs across Highly Diverged Insects

Abstract: Many genes familiar from Drosophila development, such as the so-called gap, pair-rule, and segment polarity genes, play important roles in the development of other insects and in many cases appear to be deployed in a similar fashion, despite the fact that Drosophila-like “long germband” development is highly derived and confined to a subset of insect families. Whether or not these similarities extend to the regulatory level is unknown. Identification of regulatory regions beyond the well-studied Drosophila has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(120 citation statements)
references
References 83 publications
7
112
1
Order By: Relevance
“…We previously developed SCRMshaw, an effective method to guide CRM discovery in Drosophila (Kantorovitz et al, 2009; Kazemian et al, 2011b), and recently showed that this same method can be used in a cross-species manner to identify CRMs in more diverged insect species (Kazemian et al, 2014b). SCRMshaw uses a “training set” of known Drosophila CRMs, drawn from the REDfly database (Gallo et al, 2011), to develop a computational model that can be applied to CRM discovery in either D. melanogaster or another holometabolous insect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously developed SCRMshaw, an effective method to guide CRM discovery in Drosophila (Kantorovitz et al, 2009; Kazemian et al, 2011b), and recently showed that this same method can be used in a cross-species manner to identify CRMs in more diverged insect species (Kazemian et al, 2014b). SCRMshaw uses a “training set” of known Drosophila CRMs, drawn from the REDfly database (Gallo et al, 2011), to develop a computational model that can be applied to CRM discovery in either D. melanogaster or another holometabolous insect.…”
Section: Resultsmentioning
confidence: 99%
“…SCRMshaw uses a “training set” of known Drosophila CRMs, drawn from the REDfly database (Gallo et al, 2011), to develop a computational model that can be applied to CRM discovery in either D. melanogaster or another holometabolous insect. Because we lacked a sufficient training set of late midline stage CRMs, we used a mixed mesectoderm/midline primordium/late midline training set consisting of just eight validated CRMs (“mapping1.mesectoderm,” (Kazemian et al, 2014b)) to search both the D. melanogaster and A. aegypti genomes. Despite the limitations of our training set, we were able to predict CRMs from both species over the full range of midline developmental stages (based on recovery of all eight training set members and an additional 21 known D. melanogaster CRMs; see Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FAIRE-seq studies, as well as the use of other biochemical approaches (i.e. DNAse-seq) or computational approaches for the identification of insect CREs (Kazemian et al, 2014), will also facilitate analysis of gene regulatory networks in the developing nervous system. Moreover, since FAIRE assesses chromatin states, it is anticipated that FAIRE-seq might also be applied for epigenetic analysis of sexual dimorphism in A. aegypti, an exciting prospect.…”
Section: Future Functional Genetic Studies In a Aegyptimentioning
confidence: 99%